2010
DOI: 10.1021/ct900608t
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Vibrationally Averaged Dipole Moments for the Ground and Excited C═O Stretching States of trans-Formic Acid

Abstract: Recent experimental studies of trans-formic acid (FA) in solid para-hydrogen (pH2) highlighted the importance of vibrationally averaged dipole moments for the interpretation of the high-resolution infrared (IR) spectra, in particular for the C═O stretch (ν3) mode. In this report, dipole moments for the ν3 ground (v = 0) and excited (v = 1, 2, 3, and 4) anharmonic vibrational states in trans-FA are investigated using two different approaches: a single mode approximation, where the vibrational states are obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It is interesting to note that complete vibrational averaging of the dipole moment components (over the 15 vibrational modes) has a similar effect to just torsional averaging them (over ν 15 ), indicating that motion along the CC–O–H dihedral coordinate has by far the greatest effect on the dipole moment components (see Table ). Vibrational averaging of the dipole moment is also known to be important in the related molecules, HCOOH, which has been detected in the ISM, , and HOOO, which has been searched for in the ISM …”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that complete vibrational averaging of the dipole moment components (over the 15 vibrational modes) has a similar effect to just torsional averaging them (over ν 15 ), indicating that motion along the CC–O–H dihedral coordinate has by far the greatest effect on the dipole moment components (see Table ). Vibrational averaging of the dipole moment is also known to be important in the related molecules, HCOOH, which has been detected in the ISM, , and HOOO, which has been searched for in the ISM …”
Section: Resultsmentioning
confidence: 99%
“…2528 Solvation effects were evaluated by single-point calculations on the optimized geometries at the B3LYP 6–31G* level of theory as the geometry optimizations using the conductor-like polarized continuum model (C-PCM). 28 In the calculations, ε = 4 was used for the surrounding solvent. Frequency calculations were performed to obtain free energy corrections at 298.15 K and 1 atm pressure.…”
Section: Methodsmentioning
confidence: 99%
“…More accurate and consistent dipole moments are especially predicted with use of more diffuse functions (58). From Equation (1) is noted the inverse relationship between I IR and Q 2 .…”
Section: Dipole Moments-vibrational Frequency Relationshipsmentioning
confidence: 97%
“…Indeed, "the dipole moment in a particular electronic state is some function of the internuclear distance and also depends on the orientation of the molecule" (59). Paulson et al (58) showed that the average dipole moments is correlated to the vibrational states and 6.57 D). The high-intensity nitro group frequencies come as a consequence of the modulation of the dipole moment with the N O stretches reinforced by the C C and N C stretches.…”
Section: Dipole Moments-vibrational Frequency Relationshipsmentioning
confidence: 99%